Finite Orbits of Language Operations - Charlier E; Domaratzki M; Harju T; Shallit J (Germany, 2025)
We consider a set of natural operations on languages, and prove that the orbit of any language L under the monoid generated by this set is finite and bounded, independently of L. This generalizes previous results about complement, Kleene closure, and positive closure.